How Will 401(k) Pension Plans Affect Retirement Income? - Samwick, Andrew A; Skinner, Jonathan (American Economic Review, 2004)
Two decades ago, most workers with pensions had a defined benefit (DB) plan. The employer made necessary contributions and investments to meet promised pension benefit payments when the employee retired. By 1993, the tide had turned; more than half of covered employees participated primarily in defined contribution (DC) pensions such as 401(k) plans [Employee Benefit Research Institute (EBRI), 1997]. This dramatic shift was associated as well with growing concerns about the emerging 401(k) plans. Some viewed 401(k) plans as a crisis waiting to happen when current generations, having made minimal (or no) contributions to their DC plan, retired with inadequate pension asset balances (Karen Ferguson and Kate Blackwell, 1995; Anne Willette, 1995). Another concern was that workers switching jobs would use the lump-sum distributions for houses, boats, or other purchases rather than reinvesting them in another retirement account [Ellen E. Schultz, 1995; U.S. Department of Labor (USDOL), 1998a]. In a similar vein, newly retired workers may not roll over the assets into an annuity and therefore risk spending down their retirement wealth too early (e.g., Jeffrey R. Brown and Mark J. Warshawsky, 2001). The most serious charge against 401 (k) plans,